Parents' views on childhood obesity: qualitative analysis of discussion board postings. Issue 4 (4th July 2017) - Appleton, Jessica; Fowler, Cathrine; Brown, Nicola
Abstract : Background : Childhood obesity is an increasing concern for parents and health professionals alike. Parents' perception of obesity as a current health issue for their children is important for the everyday parenting and health choices parents make. As parents are frequently going online to seek and exchange information about parenting and child health, asynchronous online discussion forums provide an opportunity to investigate their perceptions and concerns. Understanding parents' perceptions, beliefs and attitudes is important in any childhood obesity prevention and intervention. Aim : To explore parents' perceptions, perspectives and concerns regarding childhood obesity expressed on asynchronous online discussion forums. Methods : A qualitative descriptive approach using template analysis to analyse a novel data collection strategy of 34 purposefully sampled threads from two Australian-based asynchronous online discussion forums. Results : Parents on the discussion forum displayed an understanding of childhood obesity as a public health concern, the discussion incorporated issues such as providing a healthy diet and lifestyle for children. Parents shared their own opinions and experiences that challenged or conceded to the status quo of the discussion. Parents discussed the role of health professionals in obesity prevention. There were varied opinions on the relevance of health professionals, particularly nurses, monitoring of growth and risk of obesity. Conclusion : This exploratory study highlights that parents perceive childhood obesity as an important public health concern, and that they understand the key public health messages of prevention and intervention. Yet, for many it is difficult to successfully implement these messages into their everyday lives. Health professionals need to play a key role in providing non-judgemental, innovative support and advice to parents to successfully implement prevention and intervention strategies.